Divided Arsenal : - Kryder, Daniel (Cambridge University Press, 2000)
The title of this otherwise commendable piece of scholarship is misleading--rather than discussing race relations broadly, the book focuses more narrowly on relations between African Americans and the federal government. Philosophically and historically, Kryder (political science, MIT) bases his analysis on Gunnar Myrdal's An American Dilemma (1944). During World War II, he notes, the U.S. government needed to mobilize African American factory workers, farm laborers, and soldiers for the war effort. This, public officials decided, required, in part, some limited racial reform; it also required coercion to achieve the greater good. Kryder does an excellent job of examining the causes and effects of wartime race management and seeks to develop a broader understanding of how government regulates social differences in war. In doing so, to his credit, he avoids simplistic racial arguments and provides an insightful and unique analysis of this period.